Efektivitas Modifikasi Perilaku Melalui Teknik Token Ekonomi Untuk Menurunkan Perilaku Conduct Disorder pada Remaja Putri - Dini Rakhmawati; Fuad Nashori; Qurotul Uyun (Universitas Negeri Makassar, 2021)
There is a lot of research about the Conduct Disorders in male subjects, but research on the Conduct Disorders in female subjects relatively minimal. The purpose of this study is to reveal the effectiveness of behavior modification to reduce Conduct Disorders behaviour in adolescent girls using token economy techniques. Research conducted on a teenager who suffered Conduct Disorders antisocial types, female, 16 years old, had no formal education, have a level of intelligence below the average. With single-subject research design with ABA-type single-factor baseline, the reduction behavior seen from a comparison between the results of the test before and after the intervention. The results showed a decrease in the aspect of aggressive behavior (14 points), attention problems (11 points), deliquent behavior (10 points), withdrawn (10 points), social problems (5 points), anxiety/depression (4 points) , thought problems (1 point), and somatic complaints (0 points). Thus the behavior modification using token economy technique effective to decrease the Conduct Disorders in adolescent girls.